Government Domination on Television Digital Migration Regulation in Indonesia - Fasta, Feni; Armando, Ade; Triputra, Pinckey (JURNAL KOMUNIKASI INDONESIA, 2023)
This study aims to analyze the migration from analog television to digital television in Indonesia, which has been going on for more than a decade. One of them is the issue of multiplexing management rules. This multiplexing should be used for the benefit of the public because it uses public frequency. Researchers assume that there is government domination in determining policies that accommodate the interests of investors with significant capital and ignore the public interest, including the interests of small investors in the broadcasting industry. This study analyzes various regulations related to digital migration using critical policy analysis methods. The research results show that the Government continues to maintain its dominance in digital migration in Indonesia. Even though it has been sued several times and declared lost in lawsuits, through the new production rules, the Government continues to carry out the digital migration agenda and strengthen its dominance.